The quality of mathematical explanation videos: a quantitative cross-topic analysis - Thurm, Daniel (Frontiers in Education, 2025)
Mathematical explanation videos have become tremendously popular due to their easy accessibility through online platforms like YouTube. However, little is known about their quality from a mathematics education point of view. This study addresses this gap by developing a theory-based rating scheme for mathematical explanation videos and providing a first comprehensive quantitative analysis of the quality of the n = 150 most viewed English explanation videos on YouTube across three key topics (“multiplication of fractions,” “Pythagorean theorem,” “intersection of linear functions”). The results reveal that while these videos generally maintain mathematical accuracy and employ suitable mathematical language, they often fall short in elaborating on conceptual meaning, linking different mathematical representations, and connecting mathematical concepts to real-world contexts. Notably, the study also uncovers topic-specific variations in video quality. The insights derived from this analysis, along with the developed rating scheme, serve as resources for a wide array of stakeholders, including mathematics education researchers, video content creators, teacher educators, and practicing teachers.